Separation and Purification of Some Components of Iranian Saffron - Bolhasani, A.; Bathaie, S.Z.; Yavari, I.; Moosavi-Movahedi, A.A.; Ghaffari, M. (Asian Journal of Chemistry, 2016)
The isolation and purification of several components of the dried stigmas of Crocus sativus L. from Iran were performed by different methods including organic solvent extraction, absorption column chromatography, acid and alkaline hydrolysis. The progresses in the purification steps were monitored by TLC, HPLC and UV-Vis spectroscopy. IR spectroscopy was used for the characterization of purified compounds. Also the melting point of the purified compounds was determined. The separated components are crocetin, crocin (s), safranal, picrocrocin (s) and dimethylcrocetin. For the first time, the existence of three types of picrocrocin in Iranian saffron has been shown using TLC and HPLC techniques.